MATHEMATICAL MODELING OF THE THERMODYNAMIC PROCESS GAS-STEAM BUBBLES - Kutnyi, B. А.; Pavlenko, А. М. (Academic journal Industrial Machine Building Civil Engineering, 2018)
A mathematical model that considers the inertial oscillations and thermodynamic components bubbles in liquid heat exchange processes, heat transfer on the boundary bubbles. Research of the dynamic characteristics of gas-steam bubbles in various size was conducted. After the calculations its temperature, velocity, pressure steam environment inside the bubble in time, graphs bubbles size change graphs were built . It is established that each bubble size has its oscillation frequency. Calculated speed phase transients and found that it is in its maximum during the bubble oscillation. For thermodynamic properties of the surface of contact liquid and gaseous phases defined amount of solid phase formed. The research results can be applied to optimize various of technological processes related to the boil, swelling materials, and the formation of gas hydrates in a fluid cavitation.
Keywords: mathematical model; bubble; heat exchange; gas hydrate; pressure; temperature